2000
DOI: 10.1116/1.582156
|View full text |Cite
|
Sign up to set email alerts
|

Defect-permeation correlation for ultrathin transparent barrier coatings on polymers

Abstract: We begin this article by presenting a model for gas permeation through defects in barrier coatings, which is based on a very simple geometrical approach. This model allows us to evaluate permeation through a single- or through multiple circular defects in the coating, and also in special cases of size distributions and noncircular geometries. The model agrees well with published results based on complex computer simulations, and it has proven very useful in the analysis of our permeation measurements for barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
103
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(117 citation statements)
references
References 13 publications
13
103
1
Order By: Relevance
“…It is known that barrier film permeability can be affected by the chemical and physical structures of the barrier, concentration of the permeant, temperature and humidity [7,8] as well as surface defects on the barrier coating that may be induced during the deposition processes [9,10]. Da Silva Sobrinho et al [11] stated that the source of defect-driven permeation has been primarily attributed to pinhole defects [12,13] though more recent studies have shown that in the absence of pinhole defects permeation rates are still reduced by three orders of magnitude over the substrate material [14]. The remaining permeation is shown to be the result of defects in the sub-micromere to several micrometre range, produced by the surface microstructure [15] and/or low density of the films [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that barrier film permeability can be affected by the chemical and physical structures of the barrier, concentration of the permeant, temperature and humidity [7,8] as well as surface defects on the barrier coating that may be induced during the deposition processes [9,10]. Da Silva Sobrinho et al [11] stated that the source of defect-driven permeation has been primarily attributed to pinhole defects [12,13] though more recent studies have shown that in the absence of pinhole defects permeation rates are still reduced by three orders of magnitude over the substrate material [14]. The remaining permeation is shown to be the result of defects in the sub-micromere to several micrometre range, produced by the surface microstructure [15] and/or low density of the films [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…7. Based on the pinhole calculation model of A.S. da Silva Sobrinho et al [47] the pinhole size is estimated to be > 20 μm in the bilayer architecture assuming pinhole controlled moisture permeation.…”
Section: Dynamically Deposited Filmsmentioning
confidence: 99%
“…It is known that single layer encapsulation performance is limited by the presence of defects, such as cracks or pinholes in the inorganic layer [1][2][3][4]9,24,25]. Studies have shown that the use of multilayer encapsulation barriers [1,[3][4][5][6][7][10][11][12]24], deposited using techniques such as sputtering, atomic layer deposition and molecular layer deposition processes, can prevent the formation [1,[3][4][5], and propagation [3], of such defects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the use of multilayer encapsulation barriers [1,[3][4][5][6][7][10][11][12]24], deposited using techniques such as sputtering, atomic layer deposition and molecular layer deposition processes, can prevent the formation [1,[3][4][5], and propagation [3], of such defects. Water vapour transmission rate (WVTR) values for multilayer encapsulation barriers have been reported within the region of 10 -5 g m -2 day -1 (at 30 o C, 90% relative humidity (RH)) [1,6,7], and hence almost achieve the OLED protection requirement of 1×10 -6 g m -2 day -1 (at 25 o C, 40% RH) [4,5,8,12].…”
Section: Introductionmentioning
confidence: 99%